Information Technology Transformation to Support Economic Activities: A Case Study of Bukit Peramun Digital Forest - Dwi Ayu Lestari (Equity: Jurnal Ekonomi, 2024)
Bukit Peramun, located in Air Selumar Village, Belitung Regency, has been managed by the Arsel Community since 2006. In 2017, it was established as the Bukit Peramun Digital Forest ecotourism destination. This research aims to analyze the impact of information technology transformation at Bukit Peramun Digital Forest on economic activities, particularly for the local community. This study employs a qualitative method with a case study approach through observation and interviews with purposively selected informants. In 2017, the implemented information technology was QR Codes on trees. Then, from 2020 to 2022, the technology was enhanced by integrating virtual reality and augmented reality, including features like Tour 360, the Tree Recognition application, and an online reservation system through peramun.com. The results show that the information technology transformation at Bukit Peramun Digital Forest improved management efficiency and tourist experiences. Although there was a decline in revenue, foreign tourist visits showed an increase. The technological transformation also helped control visitor numbers, which positively impacted environmental conservation, with more efficient service quality and management.